2013
DOI: 10.1038/ncomms3687
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the alkaline nature of parental carbonatite melts at Oka complex in Canada

Abstract: The Earth's sole active carbonatite volcano, Oldoinyo Lengai (Tanzania), is presently erupting unique natrocarbonatite lavas that are characterized by Na-and K-bearing magmatic carbonates of nyerereite [Na 2 Ca(CO 3 ) 2 ] and gregoryite [(Na 2 ,K 2 ,Ca)CO 3 ]. Contrarily, the vast majority of older, plutonic carbonatite occurrences worldwide are dominated by Ca-(calcite) or Mg-(dolomite)-rich magmatic carbonates. Consequently, this leads to the conundrum as to the composition of primary, mantle-derived carbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…2) that are proposed to represent an early crystallization stage (Fournier, 1993) indicates Figure DR4 Although other carbonatite complexes are known to have halitebearing melt inclusions in a variety of phenocrysts (apatite, carbonates, fluorite, magnetite, perovskite; e.g., Andreeva et al, 2006;Chen et al, 2013;Panina, 2005;Sharygin et al, 2011;Zaitsev et al, 2002), none are reported to contain macroscopic segregations and/or veins with significant modal halite such as those in the St.-Honoré carbonatite. The only known exception is the natrocarbonatite lavas of the Oldoinyo Lengai volcano, where groundmass chlorides (halite and sodian sylvite), fluorite, and alkali carbonate phenocrysts (gregoryite and nyerereite) are primary magmatic minerals (Keller and Krafft, 1990;Mitchell, 1997Mitchell, , 2006.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) that are proposed to represent an early crystallization stage (Fournier, 1993) indicates Figure DR4 Although other carbonatite complexes are known to have halitebearing melt inclusions in a variety of phenocrysts (apatite, carbonates, fluorite, magnetite, perovskite; e.g., Andreeva et al, 2006;Chen et al, 2013;Panina, 2005;Sharygin et al, 2011;Zaitsev et al, 2002), none are reported to contain macroscopic segregations and/or veins with significant modal halite such as those in the St.-Honoré carbonatite. The only known exception is the natrocarbonatite lavas of the Oldoinyo Lengai volcano, where groundmass chlorides (halite and sodian sylvite), fluorite, and alkali carbonate phenocrysts (gregoryite and nyerereite) are primary magmatic minerals (Keller and Krafft, 1990;Mitchell, 1997Mitchell, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of primary melt inclusions with chloride-and alkali carbonate-rich compositions in several intrusive carbonatites ( Fig. DR5; also see Andreeva et al, 2006;Chen et al, 2013;Panina, 2005;Sharygin et al, 2011;Zaitsev et al, 2002) suggests that the current dolomitic-calcitic mineralogy of these carbonatites is not representative of their parental melts. This is supported by experiments that indicate that primary, mantle-derived carbonatitic melts have sodic dolomite compositions (Litasov et al, 2013;Wallace and Green, 1988) and generate alkali carbonate-chloride liquids by immiscibility at mantle conditions (Safonov et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the exception of alkali-rich natrocarbonatite lavas erupted at Oldoinyo Lengai in Tanzania (Dawson, 1962). However, many studies (Dawson, 1993;Zaitsev and Keller, 2006;Le Bas, 2008;Chen et al, 2013) argue that the parental carbonatite liquid is alkali-rich. Such a carbonate component could be easily lost within a few days through replacement by secondary calcite at atmospheric conditions, or the loss of alkalis can occur during melt evolution and crystallization such as that during fenitization of country rocks.…”
Section: Melting Of Carbonates At High Pressurementioning
confidence: 99%
“…Micro‐sized and nano‐sized inclusions of Na–Ca carbonates are, however, quite common in minerals from various carbonatite and ultramafic alkaline rocks, e.g. the Vulture, Kerimasi, Tinderet, and Catanda volcanoes, Guli pluton, Afrikanda, Gardiner, and Kovdor ultramafic‐alkaline complexes, and the Oka carbonatite complex . In addition, (Na,K) 2 Ca(CO 3 ) 2 and/or (Na,K) 2 Ca(CO 3 ,SO 4 ) 2 magmatic carbonates occur occasionally in kimberlite groundmass and chloride‐carbonate segregations and have been more often identified among daughter phases in melt inclusions in various minerals from kimberlites and their mantle xenoliths from different parts of the world .…”
Section: Introductionmentioning
confidence: 99%